Archaeological Practices, Knowledge Work and Digitalisation. Issue 1 (7th June 2018) - Huvila, Isto; Huggett, Jeremy
Defining what constitute archaeological practices is a prerequisite for understanding where and how archaeological and archaeologically relevant information and knowledge are made, what counts as archaeological information, and where the limits are situated. The aim of this position paper, developed as a part of the COST action Archaeological practices and knowledge work in the digital environment (www.arkwork.eu ), is to highlight the need for at least a relative consensus on the extents of archaeological practices in order to be able to understand and develop archaeological practices and knowledge work in the contemporary digital context. The text discusses approaches to study archaeological practices and knowledge work including Nicolini's notions of zooming in and zooming out, and proposes that a distinction between archaeological and archaeology-related practices could provide a way to negotiate the 'archaeologicality' of diverse practices.